Association between average triglyceride glucose-body mass index and risk of hypertension in middle-aged and elderly Chinese: A study based on Chinese CHARLS cohort data - Chuanlei Zheng; Yanhong Liu; Shaobo Zeng; Sisi Xie; Xuanning Luo; Qingfeng Wu (PLoS ONE, 2025)
Objective This study aimed to investigate the relationship between cumulative average triglyceride glucose-body mass index (TyG-BMI) and the risk of developing hypertension among middle-aged and elderly population. Methods Data were sourced from the 2012 and 2015 China Health and Retirement Longitudinal Study. The population was stratified into four exposure levels based on the quartiles of average TyG-BMI. Logistic regression analyses were employed to assess the associations between varying levels of average TyG-BMI and the risk of hypertension. Additionally, restricted cubic spline regression models were utilized to delineate the dose-response relationship between average TyG-BMI and hypertension. The contributions of fasting plasma glucose, triglyceride, and body mass index were quantified using weighted quantile sum regression to comprehensively elucidate the role of each component of TyG-BMI. Results A total of 2,841 participants aged 45 years and older were included in this study, of whom 1,302 (45.83%) were male, with a mean age of 57.63 ± 8.39 years at baseline. Throughout the follow-up period, 704 (24.78%) participants developed new onset hypertension. After adjusting for confounding variables, higher average TyG-BMI levels (from two measurements) were associated with an increased risk of developing hypertension ( Q 2: OR = 1.37, 95% CI = 1.04–1.80; Q 3: OR = 1.93, 95% CI = 1.46–2.56; Q 4: OR = 2.71, 95% CI = 2.01–3.66). The results from the restricted cubic spline regression indicated a linear association between average TyG-BMI and the risk of developing hypertension ( P for association < 0.001, P for nonlinear = 0.078). Weighted quantile sum regression revealed that BMI was a significant component of TyG-BMI, with weights of 0.666 and 0.769 in 2012 and 2015, respectively. Conclusion Average TyG-BMI emerged as an independent risk factor for new onset hypertension, exhibiting a linear correlation between the two variables. Therefore, long-term monitoring of changes in TyG-BMI should have been a critical component of hypertension prevention strategies.